Paesaggi Urbani e Rurali in Trasformazione. Contesti e Dinamiche Dell'insediamento Letti Alla Luce Della Fonte Archeologica Atti Della Giornata Di Studi Dei Dottorandi in Archeologia (Pisa, 22 Novembre 2019). XXXIV Ciclo Di Dottorato in Scienze Dell'Antichità e Archeologia Consorzio Delle Università Di Firenze, Pisa e Siena. - Fabiani, Fabio (Archaeopress, 2021)
9 papers consider landscape transformations from a diachronic perspective. The volume addresses the landscape as a complex and dynamic entity characterised by a multiplicity of phenomena in continuous transformation produced by the interaction and mutual conditioning of natural and anthropic factors.